Digital trade and development: A way forward for Africa at a continental and multilateral level - Harvey, Caitlin Megan (Department of Commercial Law, 2020)
This paper argues that digital trade can benefit developing countries and result in substantial financial gains. The regulation thereof has been at the forefront of negotiations at the multilateral level and within regions of Africa. While developing economies do not typically reap the benefits of digital progression, this paper proposes that digital trade can be developed in such a way so as to prioritise the developmental considerations of Africa specifically. Through observing the progress of the WTO platform for digital trade, namely the Work Programme on Electronic Commerce, it is seen that the multilateral regulation of digital trade is a complex task. Developing country participation at this level is essential to the sustainable development of digital trade. Within Africa, there have been notable advancements in the regulation of digital trade, evidenced by the establishment of COMESA’s Digital FTA. The considerations for the advancement of digital trade for a developing continent are numerous as not only do the traditional barriers to trade still remain a primary concern but there is also the potential threat of furthering the existing digital divide that persists between the developing and the developed world. Therefore, the paper proposes that should Africa consider developing digital trade through AfCFTA (the African Continental Free Trade Agreement) digital trade in services should be prioritised ahead of digital trade in goods. This would help overcome Africa’s trade facilitation and development challenges and advance Africa’s position in the multilateral trading system.